The Role of Islamic Religious Education in Developing Property in Students Indraprasta PGRI University, Jakarta - Arifin, M (CV ODIS, 2021)
This research is intended to see and assess the extent to which the role of the Islamic Religious Education (PAI) course and its effectiveness in shaping attitudes and moral behavior among students at the Indraprasta PGRI University (Unindra) Jakarta as one of the General Higher Education which is not affiliated with Religious Studies such as well as other universities in the country such as Syarif Hidayatullah State Islamic University of Muhammadiyah Jakarta University and or so on. This research is qualitative research with a Spradley model of data analysis method among / community students in the campus environment of the University of Indraprasta PGRI (Unindra) Jakarta. From the results of this study, it was found that the formation of morals or attitude/character through the Islamic Religious Education course at Unindra was taken with 3 (three) strategic steps, namely: (1) Moral Knowing / Learning to Know, oriented to the cognitive aspects of students to understand and mastering aspects of science regarding moral values, ethics and noble morals; (2) Moral Loving, oriented to the affective aspect of the student by giving an emotional touch to the soul and heart of the student to be able to more deeply absorb and appreciate and love these noble moral, ethical and moral values ??and feel